Annexing the Near East and the Long-Lasting Bosporan Autonomy - Halamus, Michał (Polskie Towarzystwo Filologiczne, 2018)
This article discusses the historical and geopolitical conditions that enabled the two marginal Roman client states of Nabataea and Bosporus to postpone, or avoid altogether, incorporation into the Empire. It also questions the dominant Romanocentric scholarly consensus that client states that fulfilled certain socio-political requirements – for example, those that were highly Hellenised or those which protected the imperial border against the Parthian threat – were customarily annexed. Certainly, these factors were of great importance with regards to the process of facilitating direct Roman administration. However, this perspective is inverted in this paper in an attempt to explain that Nabataea and Bosporus’ enduring autonomy was mainly due to their unique domestic character, accompanied by their remote localisation.
Keywords: Nabataea; Bosporus